1993
DOI: 10.1093/nar/21.9.2095
|View full text |Cite
|
Sign up to set email alerts
|

Consensus sequences for good and poor removal of uracil from double stranded DNA by uracil-DNA glycosylase

Abstract: We have purified uracil DNA-glycosylase (UDG) from calf thymus 32,000-fold and studied its biochemical properties, including sequence specificity. The enzyme is apparently closely related to human UDG, since it was recognised by a polyclonal antibody directed towards human UDG. SDS-PAGE and western analysis indicate an apparent M(r) = 27,500. Bovine UDG has a 1.7-fold preference for single stranded over double stranded DNA as a substrate. Sequence specificity for uracil removal from dsDNA was examined for bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 42 publications
12
70
3
Order By: Relevance
“…This scarcity of A,T mutations in mice deficient for Msh6 alone disagrees with the conclusion that Ung is responsible for a proportion of up to 52% of mutations from A and T. However, this finding hints at a collaboration between Ung and MMR (26). Ung is more active on ssDNA than dsDNA (36,37). Presumably, in normal SHM, Ung acts efficiently on ssDNA created by Msh2/Msh6 induced excision of either the U or G containing strand.…”
Section: Discussionmentioning
confidence: 79%
“…This scarcity of A,T mutations in mice deficient for Msh6 alone disagrees with the conclusion that Ung is responsible for a proportion of up to 52% of mutations from A and T. However, this finding hints at a collaboration between Ung and MMR (26). Ung is more active on ssDNA than dsDNA (36,37). Presumably, in normal SHM, Ung acts efficiently on ssDNA created by Msh2/Msh6 induced excision of either the U or G containing strand.…”
Section: Discussionmentioning
confidence: 79%
“…Slightly better release of uracil from a G:U pair is also relevent from physiological considerations where cytosine deamination will result in a G:U pair. Thus a more recent report (7) showing somewhat less efficient excision of uracil from a G:U pair (compared to an A:U pair) is still not understood. During these studies we found that excision of uracil from tetraloop regions of hairpin structures (U-loop, rp-ung, Table 2) and a penta-loop region (U-loopUS, Figure 6) is very inefficient.…”
Section: Discussionmentioning
confidence: 94%
“…However, the latter is kept to a minimum by the presence of dUTPase (dut) which maintains low levels of dUTP in the cell (1)(2)(3). UNG uses single-stranded substrates more efficiently than double-stranded substrates (4)(5)(6)(7). However, it was also reported (8) that uracil residues from some regions of single-stranded M13 DNA were removed inefficiently.…”
Section: Introductionmentioning
confidence: 99%
“…The rate differs as much as 20-fold between the ' best ' (A\T\UAA) and ' worst ' (G\CUG\C\T) sequences. Usually, but not always [34], the rate of removal is greater from U\G mispairs than from U :A pairs [35][36][37]. A low removal rate tends to be correlated with the occurrence of ' hot spots ' for mutation [36], similar to the correlation between slow spots for the repair of cyclobutyl dimers and hot spots for mutations [38,39].…”
Section: Udgsmentioning
confidence: 93%